2021
DOI: 10.1016/j.ijid.2021.04.071
|View full text |Cite
|
Sign up to set email alerts
|

The role of supporting services in driving SARS-CoV-2 transmission within healthcare settings: A multicenter seroprevalence study

Abstract: To determine the seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in healthcare workers (HCWs) based on risk of exposure to COVID-19 patients. Method: This was a SARS-CoV-2 seroprevalence cross-sectional study in risk-stratified HCWs randomly selected from three main district hospitals in Oman. Results: 1078 HCWs were included, with an overall SARS-CoV-2 seroprevalence of 21%. The seropositivity rates in low-, variable-, and high-risk groups were 29%, 18%, and 17%, respectively (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…However, the higher infection risk among support staff in the current study who have no direct patient care may point to the important role of hospital environment and community exposure ( Al-Maani et al, 2021 ). Similarly, support staff in Oman had the highest seroprevalence among all HCWPs, which was mainly attributed to community sources ( Al-Maani et al, 2021 ). Additionally, the lower perceived risk in support staff may have weaken their compliance with infection control measures.…”
Section: Discussionmentioning
confidence: 91%
“…However, the higher infection risk among support staff in the current study who have no direct patient care may point to the important role of hospital environment and community exposure ( Al-Maani et al, 2021 ). Similarly, support staff in Oman had the highest seroprevalence among all HCWPs, which was mainly attributed to community sources ( Al-Maani et al, 2021 ). Additionally, the lower perceived risk in support staff may have weaken their compliance with infection control measures.…”
Section: Discussionmentioning
confidence: 91%
“…Our study showed the comparative low risk of health care workers being infected to other categories in the community despite the increased risk of exposure at the workplace which indicates the increased risk awareness and implementation of infection prevention and control measures. However, another study we simultaneously conducted showed that the prevalence of COVID-19 infection in health care workers is a reflection of the seroprevalence in the community and that the people working in supporting services were more at risk for getting the infection than those working in high-risk areas in the hospitals such as COVID-19 wards and intensive care units (Al-Maani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that monitoring the cases of infected HCWs can be used as an early warning system for community spread and for COVID-19 admission surge. HCWs infection with SARS-CoV-2 focused interventions in minimizing health care exposure risk while the exposure in the community was proven to be more significant in driving the epidemiology of COVID-19 in health care ( 5 , 6 ). The vulnerabilities identified in the response to the epidemics and pandemics resulted in straining health care facilities and amplifying the spread of disease from the facility to the communities and vice versa ( 7 ).…”
Section: Dear Editormentioning
confidence: 99%